Bowel screening uptake during the Sars-Cov-2 pandemic. Results from a primary care audit in the United Kingdom. - Abbadessa, Francesco; Mazzocchi, Chloe (Advanced Journal of Professional Practice, 2025)
Introduction During the COVID-19 pandemic, the United Kingdom paused its bowel screening program for 6 months, a measure estimated to produce a 16% increase of avoidable colorectal cancer deaths. The aim of this audit was to observe the impact of COVID-19 on screening of a sample population in East Kent. Materials and methods Data from two primary care centres were retrospectively collected. The population sample included patients eligible for screening from 2019 to 2021. The primary outcome was uptake of screening; the secondary outcomes was the relation between gender or age and uptake. National standard of 52% was used as a comparator. Chi-square and univariate analysis were considered significant at p-value <0.05. Results and discussion Overall, 6,919 patients were invited for screening of which 5,281 positively responded (76%). In 2019, 2020 and 2021 uptake was 73%, 75%, 80% respectively. In 2021 Screening uptake was significantly higher than 2019 (p=<.00001). Subgroup analysis showed that women were more likely to engage with screening than men (77% vs 75%, p=.02) and 60-69 years old patients were less likely to be compliant compared to those >70 years old (75% vs 78%, p=.02). Conclusion This study showed a statistically significant upward trend for bowel screening uptake across 2019, 2020 and 2021. Furthermore, it highlighted that men and younger patients are less likely to engage screening compared to women and ³70 years old patients. In-depth and larger studies may be needed to determine if this positive trend is truly representative of the general population.